Design and Implementation of Portable Smart Wireless Pedestrian Crossing Control System - Saad, Wasan Kadhim; Hashim, Yasir; Jabbar, Waheb A. (IEEE, 2020)
Walking is a daily activity that requires an appropriate crosswalk as a key part of the provision of safe transportation infrastructure. In this paper, we design and develop a portable smart wireless control system for pedestrian crossing areas to manage the traffic automatically and allow the pedestrian, like school children, to cross the road safely and effortlessly. The system incorporates the concept of smart sensing to detect the presence of pedestrians and in turn, automatically controls the crosswalk traffic lights. The system composes of two Arduino microcontrollers, two infrared PIR motion sensors, and a bidirectional wireless communication link based on Bluetooth for mitigating wiring installation and transmitting the signal among traffic light units on both roadsides. The system is fabricated and implemented as a portable LED-based traffic light testbed. The developed system is tested and validated in a real environment with a 6 m road width on the university campus. According to the obtained results, the system worked effectively and fulfilled the design criteria where the communication between both sides lights is successfully functioning and the PIR sensors can accurately detect the existence of pedestrians. The developed system is cost-effective, energy-efficient, easy to install, and maintenance-free.